Contemporary human uses of tropical forested watersheds and riparian corridors: Ecosystem services and hazard mitigation, with examples from Panama, Puerto Rico, and Venezuela. (20th August 2017) - Larsen, M.C.
Abstract: Humans have long favored settlement along rivers for access to water for drinking and agriculture, transport corridors, and food sources. Settlement in or near montane tropical (and other) forests include additional benefits such as food and wood supply, and high quality water derived from watersheds where upstream human disturbance and environmental degradation are generally low. However, the advantages afforded by these floodplain and montane settings are offset by episodic risks to communities located there as floods, landslides, wildfires, volcanoes, (and tsunamis for coastal communities), cause loss of life and damage or destroy infrastructure and crops. A basic understanding of rainfall and flood patterns, as well as hillslope stability, by residents in these environments mitigates these risks. Modern global urbanization, particularly in regions of rapid economic growth, has resulted in much of this "organic" knowledge being lost, as megacities encroach on floodplains and mountain fronts. Moreover, the most likely occupants of these hazardous locations are often marginalized economically, which increases their vulnerability. Effective stewardship of river floodplains and upstream montane forests maintains a key ecosystem service, which in addition to the well-described services, (i.e. water, food, hydroelectric energy, wood products, carbon sequestration, maintenance of biodiversity, etc.) is the mitigation of natural hazards and vulnerability.